Giallo Nostalgia: Appropriations of Giallo Aesthetics in Contemporary Cinema - Baschiera, Stefano; Caoduro, Elena (Cinémas, 2021)
This article aims to engage with the ways in which contemporary global cinema looks back at the Italian giallo production of the 1970s through a series of remakes, homages and pastiches. What we define as retrogiallo differs from other examples of “retroexploitation,” where films such as Grindhouse (Rodriguez and Tarantino, 2007) and Hobo with a Shotgun (Eisener, 2011) address nostalgia for a specific kind of spectatorship, the grindhouse circuit, through conscious visual archaisms. Retrogialli present a more complex approach: instead of mimicking the imperfections of analogue indexicality, they fetishize the artisanal quality of filmmaking, displacing the stylistic features of the giallo in a highbrow context. Films such as Amer (Cattet and Forzani, 2009), The Strange Colour of Your Body’s Tears (Cattet and Forzani, 2013) and Berberian Sound Studio (Strickland, 2012) ultimately present a new opportunity to address the critical understanding of the giallo.